MENINGKATKAN KOMPETENSI GURU PAI DALAM MENGANALISA HASIL ULANGAN HARIAN - Bambang Jayadi; Arini Sadiyah; Raadliyatush Shalihah; Achmad Bagus Sugiharto (Tsaqofah: Jurnal Pendidikan Islam, 2018)
Assessment becomes a major component in the teacher's duties and work. Teachers must have the ability to carry out assessments, conduct ssecresses and use assessment results to make decisions including analyzing the results of assessments that have been done with reference to minimum standards or creterias. However, the reality on the ground is that there are still many PAI teachers who have not done their own daily repeat analysis but are helped by other teacher friends due to their lack of knowledge. This is very contrary to the teacher's main task. Therefore, the author is interested and feels responsible and needs to make efforts to improve the competence of teachers through workshops. This study uses two rounds of action research with subjects are pai teachers. Each round consists of several stages, namely: design, activities and observation and reflection. Research instruments use observation sheets and worksheets to perform exercises analyzing repeat results. Result Research shows that the workshop is one of the alternatives to the development of PAI teachers' competence in analyzing repeat results. This is evidenced by an increase in the knowledge and skills of participants. Referring to the results of the study, it is recommended that teachers should regularly participate in workshop activities because it emphasizes consultative collaborative methods so as to provide sharing opportunities between one teacher and another teacher. Schools need to provide a budget for the development of the competence of their teachers so that more professional teachers are realized.